A feasibility evaluation of the incredible Years® School Readiness Parenting programme - Hutchings, Judy; Pye, Kirstie L.; Bywater, Tracey; Williams, Margiad E. ([Madrid] : Colegio Oficial de Psicólogos de Madrid, 2020)
Parental involvement in their childrens education, including activities undertaken by parents at home and through strong links with their childrens schools, contributes to childrens academic attainment. This study examined whether it was feasible for school-based staff to deliver the Incredible Years® School Readiness parent programme (IY-SR) in schools, its acceptability to parents and teachers, its impact on home-school relationships, and preliminary programme impact. Thirty-two parents with a child in a nursery or reception class were recruited from eight schools. Group leaders and parents gave positive feedback about the programme and parental attendance on the programme was high. There were also significant increases in parents use of praise and childrens positive responses. This is the first study to demonstrate the feasibility of engaging schools to deliver the IY-SR programme as a means of promoting home-school relationships and providing parents with the skills to coach their childrens school readiness skills.
Descripción basada en Psychosocial Intervention, vol. 29, núm. 2 (may 2020), P. 83-91.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2023. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Maestros; Parentalidad; Preparación para la escuela; Viabilidad; Artículos.